USING THINK-PAIR-SHARE-STRATEGY TO IMPROVE VOCABULARY AND READING COMPREHENSION ACHIEVEMENTS OF EIGHTH GRADE STUDENTS - Kiki Rizki Amelia (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2016)
Abstract: This study was aimed to find out whether or not think-pair-share strategy: (a) improved eighth graders` vocabulary achievement, (b) improved eighth graders` reading comprehension achievement, (c) made a difference in the vocabulary and reading comprehension achievements between the experimental group students (those who were taught by using think-pair-share strategy) and those of the control group students (who were not). In conducting the study, think-pair-share strategy was applied in the experimental group, but the control group did not get any treatment. Seventy students were assigned in two groups, with 35 students in the experimental group and the other 35 students in the control group. To collect the data, vocabulary and reading comprehension tests were used. The collected data were analyzed by using paired samples t-test and independent samples t-test. The findings of the study showed that there were (a) an improvement in eighth graders` vocabulary achievement, (b) an improvement in eighth graders` reading comprehension achievement, and (c) a significant difference in vocabulary and reading comprehension achievements between the students who were taught by using think-pair-share strategy and those who were not. Therefore, think-pair-share strategy seems effective for the teaching reading as well as vocabulary. Â  Key words: think-pair-share strategy, vocabulary and reading comprehension achievements, eight graders